High cloud increase in a perturbed SST experiment with a global nonhydrostatic model including explicit convective processes. (16th July 2014) - Tsushima, Yoko; Iga, Shin‐ichi; Tomita, Hirofumi; Satoh, Masaki; Noda, Akira T.; Webb, Mark J.
Abstract Results are presented from a series of sensitivity tests in idealized global warming experiments using the global nonhydrostatic model, NICAM, in which convection at scales of 7–14 km is explicitly resolved. All have a strong positive longwave cloud feedback larger than that seen in conventional GCMs with parameterized convection. Consequently, the global mean net outgoing radiation decreases in response to increased sea surface temperatures. Large increases in high clouds with tops between 180 and 50 hPa are found, and these changes contribute the most to this longwave cloud feedback. Relative humidity and upper tropospheric temperature also increases strongly, again more so than typically seen in conventional GCMs. The magnitude of the response varies considerably between different versions of NICAM. Most of the NICAM control simulations show large overestimates in cloud fraction between 180 and 50 hPa compared to observations. The changes in cloud fraction in the upper troposphere are strongly correlated with their control values. Versions of NICAM with stronger cloud feedbacks have large positive biases in high‐top cloud amount and temperature in the free troposphere in their control simulations. The version which has the best agreement with the observations in this regard has the weakest longwave cloud feedback; however, this is still more strongly positive than that typically seen in conventional GCMs. These results demonstrate the potential for stronger high cloud fraction feedbacks in climate warming scenarios than currently predicted by conventional GCMs and highlight the potential relevance of deep convective processes.